1974
DOI: 10.1084/jem.139.5.1354
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Requirements for the Primary in Vitro Antibody Response to DNP-Ficoll

Abstract: Antibody formation to most antigens requires collaboration between T lymphocytes and B lymphocytes, but certain antigens (e.g., polymerized bacterial flagellin, bacterial lipopolysaccharides, polyvinylpyrrolidone, levan [1][2][3][4][5]) induce antibody synthesis in the absence of detectable numbers of T lymphocytes, and hence are termed "T independent". We have examined the in vitro response of mouse spleen cells to e-2,4 dinitrophenyl (DNP)-lysyl-subsfituted Ficoll (a synthetic polymer of sucrose and epichlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

1975
1975
1983
1983

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(52 citation statements)
references
References 15 publications
2
50
0
Order By: Relevance
“…The in vitro PFC response to DNP-Ficoll has been shown to be independent of T lymphocytes in adult (9) and neonatal (Mosier, unpublished experiments) mice. The response to SRBC or TNP-SRBC is quite dependent upon the presence of T lymphocytes (15) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The in vitro PFC response to DNP-Ficoll has been shown to be independent of T lymphocytes in adult (9) and neonatal (Mosier, unpublished experiments) mice. The response to SRBC or TNP-SRBC is quite dependent upon the presence of T lymphocytes (15) .…”
Section: Resultsmentioning
confidence: 99%
“…Preparation of DNP-Ficoll has been described recently (9). DNP,,Ficoll (32 mol DNP/400,000 average mol wt of Ficoll) was used for these experiments .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of ribavirin on the primary in vitro PFC response to SRBC was determined by the method of Mosier et a1 (28). Primary in vitro PFC were generated in the presence of varying dilutions of ribavirin (moles/liter) and the number of PFC/culture well was determined on day 5.…”
Section: Evaluation Of Immunologic Statusmentioning
confidence: 99%
“…TNP-Ficoll, a prototypic TI-2 antigen, requires Ia + macrophages (14), a specific subset of B cells (Lyb-5 +) (15), and elicits a response in congenitally athymic mice (16). The response of nu/nu mice to TI-2 antigens suggested that T cells were not required for specific antibody production.…”
mentioning
confidence: 99%